Innocube / Aiman Iman Shaifuddin ... [et al.] - Shaifuddin, Aiman Iman; Alias, Juliani; Fairuz, Fida Naziha; Suhaimi, Nuramyshazlianna; Hardy Azmir, Batrisyia Syahirah; Samsudin, Siti Nurizzati Atirah (2023)
These days, watching films and online series has grown in popularity from various walks of life. Previously, we would watch a movie on TV or in theatres. We can view them on TVs, laptops, and phones these days. It's also because they're a great way to unwind following a demanding workday. Additionally, it's now simpler for us to find what we want to watch thanks to the proliferation of online streaming services like Netflix and YouTube. Usually, some common devices used to watch movies include devices such as computers, tablets, smartphones, TVs, game consoles, and streaming devices. Usually more users have smartphones and use their smartphones for watching films and movies. Unfortunately, with the use of smartphones it minimizes the resolution or clarity of the film that they watch. While if they use tv’s and laptop it could be a little bit pricey for the user. So, with the existence of magnifiers magnifies the image or on the screen and makes it more visible to users. Our company uses the concept of a convex lens. Lenses can generally be divided into two major groups: convex lenses and concave lenses. Depending on the type of lens, the light passing through it can travel along very different trajectories and produce images of different sizes and orientations. The magnifying screen of the smartphone is one big convex lens, which means that the surfaces of this lens are slightly outwardly curved and it works like an ordinary magnifying glass which is the concept of this technology is a new product development (NPD) that follows the current trend and how our services can help to solve the customer’s worries. In addition, the development process involves addition of a compartment and some other function as some step of development. A survey has been conducted by our team members and is being distributed to a few respondents to make sure whether they are aware of the uses of phone magnifiers in this era and how effective the development of normal phone magnifiers is to the new development which is Innocube to help user in their usage in daily life. From the data we obtained, 91.4% of respondents love the idea of innovation for this product. Thus, in order to meet consumer expectations and maintain the application's smoothness, we will continue to improve our products and services based on input from our respondents.